The Use of Macromedia Flash Animation to Enhance Students’ English Writing Skill at the Seventh Grade of SMP Yapis 1 Fakfak-West Papua - Wa Lisda; Muhammad Asfah Rahman; Haryanto Atmowardoyo (ELT Worldwide: Journal of English Language Teaching, 2015)
This research is conducted to find out: (1) whether the use of  Macromedia Flash Animation  enhance  students'  writing  skill  or  not;  (2)  the  students'  interest  in English writing class using Macromedia flash animation; (3) whether student's interest have relationship to student's writing ability or not. The research employs the quasi-experimental method. The sample consists of 51 students which belongs to two groups; 27 students in the experimental group and 24 students in the control group. The data are collected by writing test (pre-test and post-test) and questionnaire which is analyzed through SPSS 20.0. In conducting the research, the researchers applies Macromedia Flash Animation as the medium to the experimental group while the teacher in the control group uses power point presentation. The research results indicated that Macromedia Flash Animation can enhance students' English writing skill at the seventh-grade students of SMP Yapis 1 Fakfak-West Papua in academic year 2014/2015. Although the mean score of the experimental group is higher than the mean score of the control group, it does not show a significant difference (73.93>70.33). Therefore, based on pair test, the result shows that the mean score of pre-test and post-test in the experimental group are significantly different (55.41-73.93). Moreover, based on the students' response on  the  questionnaire,  it  is  found  that  the  mean  score  is  80.15  which  was categorized “interested”. The Pearson’s r for correlation shows that the correlation coefficient between students’ interest and students’ writing ability is 0.891, with the sig. (2 tailed) value is less than 0.05 indicates that there is a strong, significant and positive correlation between students’ interest and students’ writing ability. Specifically,  the  research  result  indicates  that  Macromedia  flash  animation  is interesting and effective to enhance students’ writing skill. Key words: Macromedia flash animation, writing skill, interest.